2005
DOI: 10.1080/09638230500347889
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and empirical models around caring for someone with an eating disorder: The reorganization of family life and inter-personal maintenance factors

Abstract: Background: Previous theoretical models regarding family functioning have proposed that dysfunctional family interactions may play a causal role in the development of eating disorders. Such models, while historically important, have been unhelpful in blaming families and are poorly supported by empirical evidence. Aims: The aim of this paper was to expand and develop models around familial patterns which may be more clinically valuable. Method: Recent empirical and theoretical evidence around family's experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 31 publications
7
74
0
1
Order By: Relevance
“…Siblings further indicated that the eating disorder interfered with eating together at family meals and this resulted in a lack of normalcy in their family. Other review papers on eating disorders have similarly pointed to the ways in which eating disorders interrupt and disrupt family meals (Whitney & Eisler, 2005). On the other hand, siblings recounted building a strong bond with their affected sibling as a result of them living with AN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Siblings further indicated that the eating disorder interfered with eating together at family meals and this resulted in a lack of normalcy in their family. Other review papers on eating disorders have similarly pointed to the ways in which eating disorders interrupt and disrupt family meals (Whitney & Eisler, 2005). On the other hand, siblings recounted building a strong bond with their affected sibling as a result of them living with AN.…”
Section: Discussionmentioning
confidence: 97%
“…The significant disability associated with AN necessitates that the majority of affected individuals rely on caregivers, typically close family members, for emotional, instrumental and financial support. Although the lifethreatening nature of AN may compel family members to organize their life around supporting and accommodating their loved ones to ensure their survival (Eisler, 1995;Whitney & Eisler, 2005), the impact on the family has only recently garnered the attention of researchers and clinicians. The limited body of literature regarding caregivers of individuals with eating disorders suggests that they experience significant distress as a result of their caregiving role (CotteeLane, Pistrang, & Bryant-Waugh, 2004;Haigh & Treasure, 2003;Huke & Slade, 2006;Perkins, Winn, Murray, Murphy, & Schmidt, 2004;Santonastaso, Saccon, & Favaro, 1997;Treasure, Murphy, Szmukler, Todd, Gavan, & Joyce, 2001;Whitney, Murray, Gavan, Todd, Whitaker, & Treasure, 2005) and that it may be exacerbated by stigma, blame and shame (Highet, Thompson, & King, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we have found that some carers are somewhat sceptical and reluctant to be involved in family work (Whitney & Eisler, 2005). The workshop format serves to defuse some of the guilt and stigma attached to having someone with an eating disorder in the family.…”
Section: Common Concerns About Interventions With Familiesmentioning
confidence: 98%
“…The schedule of the workshop follows that recommended for adult learning with plenty of time for reflection and observation. We encourage the use of writing in between the sessions to foster self-reflection as used in our earlier work (Whitney & Eisler, 2005).…”
Section: The Format and Protocol Of The Workhopmentioning
confidence: 98%
See 1 more Smart Citation